Inserting a VA-ECMO cannula through an inferior vena cava filter during extracorporeal cardiopulmonary resuscitation - Genhua Mu; Rongliang Xu; Yiyun Wang; Chun Pan; Jianfeng Xie (International Journal of Emergency Medicine)
Abstract Venoarterial extracorporeal membrane oxygenation (VA-ECMO) has been utilized to treat massive pulmonary embolism (PE) accompanied by cardiac arrest or refractory cardiogenic shock. Our team opted for a femoral-femoral approach for vascular cannulation, using drainage and return cannulas in the common femoral vein and artery, respectively. However, femoral venous cannulation can be limited or challenging due to the presence of thrombus in the inferior vena cava (IVC), making the insertion of the drainage cannula via the femoral vein difficult. We present the case of a patient with massive PE who underwent aspiration thrombectomy and insertion of an IVC filter, followed by the initiation of VA-ECMO for cardiac arrest. We successfully inserted a femoral venous return ECMO cannula through the inferior vena cava filter during extracorporeal cardiopulmonary resuscitation. The patient stabilized with these interventions and ultimately achieved a favorable outcome with normal neurological status.